METABOLIC BONE DISEASE OF PREMATURITY – SURVEY OF CURRENT NEONATAL INTENSIVE CARE APPROACHES - Yiling, See Toh; Leong, Annie; Azanan, Mohamad Shafiq; Han, Lim Tse; Samingan, Nurshadia; Jalaludin, Muhammad Yazid; Zaini, Azriyanti Anuar (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Metabolic bone disease of prematurity (MBDP) requires both calcium and phosphate for prevention and treatment. However, clinicians often focus on phosphate and vitamin D supplementation, neglecting calcium deficiency in nutrition. This study evaluates MBDP management in the neonatal care unit in a quaternary hospital in Malaysia. METHODOLOGY We conducted a retrospective review of MBDP cases referred to paediatric endocrinologists at University Malaya Medical Centre from 2019 to 2025. We extracted data from electronic medical records and monitoring charts, and we obtained input from pharmacists and dietitians regarding mineral supplementation in enteral and parenteral nutrition. RESULT The study involved 22 subjects, primarily infants with extremely low birth weight (ELBW), with a median birth weight of 705 grams (interquartile range: 600–833 grams). All infants were born before 32 weeks of gestation, and most were born before 28 weeks. The mean age at referral was 66.3 ± 33.43 days. Upon referral, all subjects exhibited low phosphate and high alkaline phosphatase levels. Only 15 subjects had their parathyroid hormone (PTH) levels checked, and PTH testing was conducted more frequently after referrals to endocrinology. Fifteen subjects showed radiological evidence of MBDP, and six of them had fractures. Routine screening revealed hypophosphatemia, hyperphosphatasia, and normocalcemia at least one month prior to referral. Most subjects were presumed to be treated with oral phosphate and vitamin D supplements; however, many later showed elevated PTH levels, suggesting secondary hyperparathyroidism. None of the subjects were found to be vitamin D deficient. Prolonged fasting was identified as a significant risk factor for severe MBDP. Most subjects received low calcium levels alongside relatively high phosphate in parenteral nutrition. Less than 25% of the infants received Human Milk Fortifier (HMF) despite being primarily breastfed. Only two subjects received calcium supplements. CONCLUSION The study highlights gaps in understanding mineral supplementation in MBDP and the underutilization of PTH screening. Routine phosphate supplementation without addressing calcium deficiency worsens secondary hyperparathyroidism and MBDP. The study recommends routine HMF usage, earlier PTH screening, and standardized guidelines to improve MBDP management.